HUBUNGAN GOOD UNIVERSITY GOVERNANCE TERHADAP KINERJA MANAJEMEN KEUANGAN PERGURUAN TINGGI - Wahyudin, Agus; Nurkhin, Ahmad; Kiswanto, Kiswanto (UNIVERSITY OF MERDEKA MALANG, 2017)
The pattern of financial management institution had to be accountable as one indicator of university management assessment as a whole. This study examined the management of higher education in terms of the implementation of Good University Governance (GUG). GUG concept was adopted from the concept of good corporate governance. The samples were state universities in Central Java and Yogyakarta using purposive sampling technique. Data analysis used was the Structural Equation Model (SEM) analysis based on Path Analysis. The results showed that GUG directly influenced the Cultural Organization (CO), and Organizational Structure (OS) affected the Financial Management Performance (FMP). However, GUG did not directly influence FMP, OS, and PM (Planning Management). PM and OS were proven not directly influence the FMP. Other evidence found was the indirect effect of GUG to FMP through OS, PM, and CO. The conclusions of this research were GUG would increase CO and OS and would further increase FMP. Thus, universities should consider the implementation of GUG to increase the performance of financial management.